2008
DOI: 10.1016/j.yexcr.2008.01.036
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of secretion during sea urchin embryonic skeleton formation

Abstract: Skeleton formation involves secretion of massive amounts of mineral precursor, usually a calcium salt, and matrix proteins, many of which are deposited on, or even occluded within, the mineral. The cell biological underpinnings of this secretion and subsequent assembly of the biomineralized skeletal element is not well understood. We ask here what is the relationship of the trafficking and secretion of the mineral and matrix within the primary mesenchyme cells of the sea urchin embryo, cells that deposit the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…Calcein is a fluorescent calcium-binding dye that does not permeate through membranes, channels, or pumps. Calcein was shown to enter the PMCs and label intracellular calcium and the spicules (22,24,25,28,29). In a correlative study, it was shown that calcein labeling does faithfully track calcium distributions (24), and this is assumed to be the case in the study presented here.…”
supporting
confidence: 50%
“…Calcein is a fluorescent calcium-binding dye that does not permeate through membranes, channels, or pumps. Calcein was shown to enter the PMCs and label intracellular calcium and the spicules (22,24,25,28,29). In a correlative study, it was shown that calcein labeling does faithfully track calcium distributions (24), and this is assumed to be the case in the study presented here.…”
supporting
confidence: 50%
“…The rays elongate rapidly for Ϸ3 days, while the existing rays thicken. ACC is most probably introduced into the mineralization site by the cells in vesicles that fuse with the syncytial membrane (15). The spicule is tightly surrounded by this membrane, with no interstitial water solution detectable at any stage (16).…”
mentioning
confidence: 99%
“…Many genes, including many of the downstream effector genes that were identified in the present study, show non-uniform patterns of expression within the PMC syncytium, with high levels of transcripts accumulating at sites of skeletal rod growth (Harkey et al, 1992; Guss et al, 1997). There is evidence from the expression of transgenes within the PMC syncytium that mRNAs remain localized predominantly in the PMC cell body in which they were synthesized (Harkey et al, 1995;Makabe et al, 1995;Wilt et al, 2008), a finding which suggests that local variations in mRNA abundance within the syncytium arise through the local regulation of gene transcription, rather than by an indirect mechanism (e.g. the diffusion and selective trapping of mRNAs).…”
Section: Regulation Of the Pmc Grn By Extrinsic Signalsmentioning
confidence: 99%